Flock structure, level of production, and marketing of three Ethiopian goat types kept under different production systems - Tadesse, D.; Urge, Mengistu; Animut, G.; Mekasha, Yoseph (2014)
This study was conducted to characterize three Ethiopian indigenous goat types in terms of their composition and dynamics, productivity, and marketing. A set of semi-structured questionnaire was used to collect information from 155 goat owners based on single-visit-interviews. The study indicates that breeding females constituted the largest average flock composition followed by weaners and kids. Goat owners in the study areas relied mainly on births and purchases to build their flock while sales and deaths were the major routes of disposal. Lower commercial offtake (28%) and higher mortality (24%) rates were estimated for all study areas but the figures were lower in pastoral and agro-pastoral systems. On average, female goats in the study area gave first birth at the age of 1.4 years, kidded every 8.6 months and stayed on production/kidding for about 5 years, giving daily milk yield of 0.37 liter. Based on the estimates given by respondents, Somali and highland goats were characterized to have bigger age at first kidding and longer kidding life time, respectively. For other traits such as kidding interval and daily milk yield, no significant performance difference was observed among the goat types. In all study areas, goats were sold mainly at the farm gate when money is needed to buy grains and other farm inputs. Average age at sale/slaughter of male goats was about 1.4 years. Consumers, producers, traders, butchers and brokers were the major buyers of live goats in the study areas. The participation of goat producers in the market was constrained by seasonality of market, low price, and lack of market information and infrastructure.